Analysis of cytochrome P450 gene polymorphism in a lupus nephritis patient in whom tacrolimus blood concentration was markedly elevated after administration of azole antifungal agents. (12th September 2012) - Fujita, Y.; Araki, T.; Okada, Y.; Aomori, T.; Shimizu, R.; Tomizawa, T.; Hiromura, K.; Nojima, Y.; Nakamura, T.; Yamamoto, K.
Summary: What is known and Objective:  Both itraconazole (ITCZ) and voriconazole (VCZ) are potent inhibitors of cytochrome P450 (CYP) 3A, and their effects have been reported to be equal. However, ITCZ is metabolized by CYP3A, whereas VCZ is mainly metabolized by CYP2C9 and CYP2C19 and only partially by CYP3A. We experienced the case of a patient who showed a 5‐fold increase in trough levels of tacrolimus (FK) level after switching from ITCZ to VCZ. Our objective is to discuss the mechanism of the increase drug–drug interaction in terms of serum concentration of the azole drugs and patient pharmacogenomics. Case summary:  A 53‐year‐old woman was treated with FK (1 mg/day) for lupus nephritis. Because fungal infection was suspected, she received ITCZ (100 mg/day). When ITCZ was replaced with VCZ (400 mg/day), the blood concentration of FK increased markedly from 6·1 to 34·2 ng/mL. During coadministration with FK, the levels of ITCZ and VCZ were 135·5 ng/mL and 5·5 μg/mL, respectively, with the VCZ level around 3‐fold higher than the previously reported level (1·4–1·8 μg/mL). Her CYP genotypes were CYP2C19*1/*2, CYP3A4*1/*1 and CYP3A5*3/*3 . What is new and Conclusion:  The patient was a CYP2C19 intermediate metabolizer (IM) and deficient in CYP3A5. The increase in plasma VCZ level appears to have been at least in part, associated with the CYP2C19 IM phenotype. One possible explanation for the marked increase in blood FK concentration was increased inhibition of CYP3A because of the impaired metabolism and subsequent increased plasma concentration of VCZ. This case shows that the severity of drug interactions may be influenced by metabolic gene polymorphism.